Enhanced Polar Outflow Probe Ionospheric Radio Occultation Measurements at High Latitudes: Receiver Bias Estimation and Comparison With Ground‐Based Observations. Issue 2 (6th February 2018) - Watson, C.; Langley, R. B.; Themens, D. R.; Yau, A. W.; Howarth, A. D.; Jayachandran, P. T.
Abstract: This paper presents validation of ionospheric Global Positioning System (GPS) radio occultation measurements of the GPS Attitude, Positioning, and Profiling Experiment occultation receiver (GAP‐O). GAP is one of eight instruments comprising the Enhanced Polar Outflow Probe (e‐POP) instrument suite on board the Cascade Smallsat and Ionospheric Polar Explorer (CASSIOPE) satellite. One of the main error sources for certain GAP‐O data products is the receiver differential code bias (rDCB). A minimization of standard deviations (MSD) technique has shown the most promise for rDCB estimation, with estimates ranging primarily from −40 to −28 total electron content units (TECU = 10 16  el m −2 ; 21.6 to 15.1 ns), including a long‐term decrease in rDCB magnitude and variability over the first 3 years of instrument operation. In application of the MSD method, the sensitivity of bias estimates to ionospheric shell height are as large as 4.5 TECU per 100 km. MSD calculations also agree well with the "assumption of zero topside TEC" method for rDCB estimate at satellite apogee. Bias‐corrected topside TEC of GAP‐O was validated by statistical comparison with topside TEC obtained from ground‐based GPS TEC and ionosonde measurements. Although GAP‐O and ground‐based topside TEC had similar variability, GAP‐O consistently underestimated the ground‐derived topside TEC by up to 7 TECU. Ionospheric electron density profiles obtained from Abel inversion of GAP‐O occultation TEC showed good agreement with F region densities of ground‐based incoherent scatter radar measurements. Comparison of GAP‐O and ionosonde measurements revealed correlation coefficients of 0.78 and 0.79, for peak F region density and altitude, respectively. Key Points: GAP‐O provides high‐resolution radio occultation and topside TEC measurements of the ionosphere, primarily at northern high latitudes GAP‐O receiver bias estimates are in the range of ‐40 to ‐28 TECU, with a long‐term decrease in bias magnitude and day‐to‐day variability F region ionospheric density profiles retrieved from inversion of occultation TEC correlate well with ISR and ionosonde measurements